METHOD OF EARLY CHILDHOOD SEXUAL EDUCATION IN INDONESIA - Eti Rimawati; Sri Achadi Nugraheni (Faculty of Public Health, Andalas University, 2018)
The issue of violence or sexual abuse in children is one of the reproductive health problems facing Indonesia. Some efforts to provide early child sex education have been done through teachers, parents and children. This study aims to describe the method of sex education that has been done to improve early childhood understanding related to reproductive health. The review process is done by searching the results of research can be accessed through google scholar in the form of journals, proceedings and scientific thesis, with the keyword